Implementation of E-Commerce Based on Website for Eel Seed in Lebak Banten - Wiwin Windihastuty; Taqwa Putra Purnomo Sidi (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Banten Eel Farmers Group is a group of eel seed catcher communities on the coast of Sukamanah Village, Lebak Regency, Banten. In effort to sell their catch, they are constrained by promotion issues, marketing is not yet open, only relying on word of mouth, this has resulted in many cultivators who do not know the existence of eel seeds in Sukamanah Village on the other hand, many eel seeds that have been caught have died because they are not properly maintained. Until now, the Banten Eel Farmers Group has only provided a simple place to store the catch. From this background, this study aims to create an e-commerce website that has marketing and promotion features, the latest news about eels and knowing the shipping status. Researchers use Business Model Canvas (BMC) to analyze data collected through interviews and observations. The information obtained is then used to analyze the e-commerce system, implement search engine optimization, and carry out the Fishbone marketing strategy, namely product, price, place and promotion (4P). The results of this study produced an e-commerce website design that has several functions such as marketing and selling products and services offered through the website and is also integrated with social media such as Instagram and Whatsapps.